2020
DOI: 10.1038/s41416-020-01173-0
|View full text |Cite
|
Sign up to set email alerts
|

Tumour acidosis evaluated in vivo by MRI-CEST pH imaging reveals breast cancer metastatic potential

Abstract: Background Tumour acidosis is considered to play a central role in promoting cancer invasion and migration, but few studies have investigated in vivo how tumour pH correlates with cancer invasion. This study aims to determine in vivo whether tumour acidity is associated with cancer metastatic potential. Methods Breast cancer cell lines with different metastatic potentials have been characterised for several markers of aggressiveness and invasiveness. Murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 62 publications
0
44
1
Order By: Relevance
“…Differences in position may possibly account the difference observed between both techniques. It is also worth to mention that the basal pHe values (before treatment) measured in our study for the 4T1 tumor model were higher than 7.0 (for CEST-MRI and 31 P-NMR) while a recent study that compared several breast cancer cell lines suggested lower pHe values for the same model (6.96 ± 0.03) [ 27 ]. Different experimental conditions may potentially explain these differences: different conditions of cell culture before inoculation and time-window for the MRI study during the tumor growth.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Differences in position may possibly account the difference observed between both techniques. It is also worth to mention that the basal pHe values (before treatment) measured in our study for the 4T1 tumor model were higher than 7.0 (for CEST-MRI and 31 P-NMR) while a recent study that compared several breast cancer cell lines suggested lower pHe values for the same model (6.96 ± 0.03) [ 27 ]. Different experimental conditions may potentially explain these differences: different conditions of cell culture before inoculation and time-window for the MRI study during the tumor growth.…”
Section: Discussionmentioning
confidence: 50%
“…Different experimental conditions may potentially explain these differences: different conditions of cell culture before inoculation and time-window for the MRI study during the tumor growth. We also noticed that the anesthesia used was different: ketamine/xylazine in the reference study [ 27 ] and isoflurane in the present study. As ketamine/xylazine is known to induce a rapid drop in tumor perfusion and oxygenation [ 50 , 51 , 52 ], we hypothesize that this experimental factor may potentially contribute to subtle difference in glycolytic activity and pHe values recorded for the same tumor model.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…These include microelectrodes, which are invasive and imprecise, positron emission tomography approaches, which report on a composite of pH e and pH i , and genetically encoded or injectable optical imaging techniques, which are often not clinically relevant and remain limited by the lack of sufficiently specific near-infrared pH e probes. 1,2 In this issue of the British Journal of Cancer, Anemone et al 7 used magnetic resonance imaging (MRI)-based, pH-sensitive chemical exchange saturation transfer (MRI-CEST) 8,9 to demonstrate that extracellular acidosis correlates with tumour metastatic behaviour in vivo. Employing spontaneous BALB-neuT mammary tumours as well as syngeneic engrafting of metastatic and non-metastatic mammary cancer cell lines in BALB/c mice, they created spatial pH e maps of primary tumours and defined an acidity score highlighting pH e heterogeneity.…”
Section: Mainmentioning
confidence: 99%
“…While earlier studies have proposed a correlation between invasiveness and extracellular acidity in tumours, 12,13 the work by Anemone et al 7 takes this an important step further by combining the precision and clinical potential -MRI-CEST has been used in patients 14 of MRI-CEST with studies of mammary cancer phenotype. Notably, they found that the tumour acidity score correlated not only with metastasis, but also with the expression of cancer stem cell markers in the tumour tissue, extending earlier reports that stemness in glioma models is dependent on an acidic niche pH e .…”
Section: Mainmentioning
confidence: 99%